The Tanggung Jawab Hukum Notaris dalam Mengeluarkan Cover Note terkait Jual Beli Rumah - Ni Made Trisna Dewi (Fakultas Hukum, Universitas Warmadewa, 2023)
Taking care of various interests such as buying and selling, leasing and other agreements, of course, now requires the services of a notary in it, the notary in this case is responsible for the files that have been issued for the terms and conditions of a particular problem or interest, in this case the notary is especially responsible for issuing or issuing covers. note. In the process of buying and selling a house, there is a notary's role in fulfilling the necessary documents, in line with his role and also his authority to make a real deed there are also responsibilities and legal consequences if there are mistakes that violate the law or to the detriment of the parties involved in terms of This is especially related to publishing or making cover notes. Based on this, the authors put forward the formulation of the problem, namely, first, what are the legal responsibilities of a notary in issuing cover notes related to buying and selling houses? and secondly, what are the legal consequences if the notary does not include the cover note at the time of signing the sale and purchase of the house? This research is an empirical research with the sources and types of data used, namely library data sources and field data sources, as well as the types of data used consisting of primary and secondary data, while the data collection technique was carried out by means of documentation studies from literature materials and interviews. to informants, and data analysis was analyzed discretely and qualitatively by compiling the data obtained. The results of this study indicate that the legal responsibility of a notary in issuing a cover note relating to the sale and purchase of a house is to issue a cover note on the authority of a notary according to UUJN (article 15). Make authentic deeds regarding all actions, agreements, and provisions required by laws and regulations and/or which are desired by interested parties, to be stated in an authentic deed, guarantee the certainty of the date of making the deed, save the deed, provide grosse, copies and quotations of the deed, all as long as The making of the deed is not assigned or excluded to officials or other people determined by law.